2021
DOI: 10.1101/2021.10.19.21265183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic analysis of the abundance and composition of antibiotic resistance genes in hospital wastewater in Benin, Burkina Faso, and Finland

Abstract: Antimicrobial resistance (AMR) is one of the greatest global threats to human health, but substantial gaps in AMR data exist in West African countries. To obtain in-depth data, we explored the presence of antimicrobial resistance genes (ARGs) in the hospital wastewaters (HWW) of nine hospitals in Benin and Burkina Faso and, for comparison, of four hospitals in Finland. The highest total relative abundance of ARGs in HWWs was observed in Benin and the lowest in Finland. HWW resistomes were more similar to each … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…More microbiological research is needed to determine if resistance genes are transmitted across these domains between human and animal species, but the lack of sanitation, and the potential flow of contaminated water, means that resistant infections are spreading. For example, Markkanen et al ( 13 ) identified a worryingly high abundance of AMR genes in hospital water in the region.…”
Section: Resultsmentioning
confidence: 99%
“…More microbiological research is needed to determine if resistance genes are transmitted across these domains between human and animal species, but the lack of sanitation, and the potential flow of contaminated water, means that resistant infections are spreading. For example, Markkanen et al ( 13 ) identified a worryingly high abundance of AMR genes in hospital water in the region.…”
Section: Resultsmentioning
confidence: 99%
“…Important studies have described AMR in water and effluents [3][4][5][26][27][28][29][30][31][32][33][34][35][36], but lack of a consensus set of tools to harmonize methodologies and analyses across multiple groups' efforts (from water collection and laboratory processing to bioinformatic analysis and reporting) leaves us without a ready, common source of information to support local, national and global AMR monitoring of the environment. Metagenomic approaches provide valuable surveillance of species such as Mycobacterium, Mycoplasma and Neisseria (as shown in Figure 11), but for surveillance of NARMS critically important gene targets, metagenomics should be coupled with microbial pre-enrichment using relevant bacterial growth media.…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial identification of mcr-1, a range of gene variants (mcr-1 to mcr-10) have been discovered in numerous bacteria, including ESKAPE pathogens. 14 The occurrence of these genes on mobile genetic elements such as plasmids has also aided in the dissemination of mcr genes across socioecological borders, with gene variants being detected in humans, livestock, agricultural soils, water, wastewater, and wildlife. 15 Furthermore, an extensive survey using publicly available metagenomic data sets showed a global distribution of mcr genes with differences in the abundance of mcr variants occurring based on time and geographic location.…”
Section: Introductionmentioning
confidence: 99%